H.C. Andersens Iisjomfruen und die Unterhaltungsliteratur des 19. Jahrhunderts - Seiler, Thomas (Folia Scandinavica Posnaniensia, 2016)
H.C. Andersen’s fairy tale The Ice Maiden is in many ways very modern, especially when we take into account its formal and rhetorical devices. The narrative is not invented by the author as the story is compound of travel journeys, popular readings of the time and so on. Andersen himself indicated some of his sources. In the following paper I would like to discuss the relationship between the fairy tale and the so called „Gebirgserzählung“ from the 18th and 19th century, which was extremely popular at the time. While the core of a “Gebirgserzählung” often consists in a young couple, that after many troubles in the end comes happily together, this is not the case in The Ice Maiden, as Andersen let the protagonist die. It looks as if Andersen would argue in favour of predetermination, based on Christian belief. However, this conclusion is not convincing because it fails to explain the obvious injustice of Rudy’s fate. In what follows I suggest a rhetorical explanation of the protagonist’s death. In such a view Rudy’s death is not to be understood as predetermined, but as a result of Andersen’s fear of his own modernity. What he demonstrates is how an entire story can be the result of other stories, how literature is based on literature. But the author himself seems not to be mature for this insight and that’s the reason why he let the protagonist die.